Human capital development strategy on go-public manufacturing companies in Indonesia - Saban Echdar (Universitas Hayam Wuruk Perbanas, 2015)
This study analyzes the development of human capital strategy in go-public manufactur-ing companies, examining the several effects of variables, and also the effect of interven-ing variables on the development of human capital. The population consists of 151 go-public manufacturing companies listed on the Stock Exchange. The purposive sampling method was used and 12 companies were taken in which 10 of respondents from each company consisting of managers and staff, and the data were analyzed using Structural Equation Modeling (SEM). It shows that the first, the external environment has positive and significant effect on the planning and management of human resources, education and training, and the development of human capital, but has no significant effect on improving employees, employee performance and recognition, and employee satisfaction. Second, the internal environment has a positive and significant impact on the planning and management of human resources, employee improvement, education and training, employee performance and recognition, employee satisfaction, and the development of human capital. Third, planning and human resource management, employee improve-ment, education and training, employee performance and recognition, and employee satisfaction have a significant and positive effect on the development of human capital.